Financial leverage, firm growth and financial strength in the listed companies in Malaysia / Rodilah Ali - Ali, Rodilah (2017)
This study was conducted is to examine effect of financial leverage to the firms growths and financial strength in Malaysia. This study focus on 30 conglomerates companies that listed in BURSA Malaysia. This study sought to examine the impact of leverage for the period of 8 years from 2009 to 2016. In this study, panel regression is used in order to test the hypotheses of this study using Statistics/Data Analysis (STATA) software. Using asset growth, profit growth sales growth and financial strengths independent variables, the findings shows that there is positive relationship between leverage and profit growth as well as the sales growths. As for the asset growths and financial strength, there is a inverse relationship.